Evidence of seismicity induced by water level changes at the Mosul Dam reservoir and implications on the hydraulic diffusivity - Al-Saigh, Nabeel Hameed (Journal of Mediterranean Earth Sciences, 2015)
The relationship between Reservoir level and earthquake frequency at Mosul Dam's Reservoir shows an evident increases in seismicity following the yearly maxima in water level, with growths of epicentral area (hydraulic diffusivity), at about 9.3x104 cm2/sec. This value corresponds to permeability of about 8.4 x 10-11 cm2. Seismicity concentration with time and space of their occurrences was obvious. A trend of 75.71 m/km of seismicity concentration towards the east and 9.676 m/km with depth was observed.